Analisis Keterampilan Variasi dalam Mata Kuliah Microteaching pada Mahasiswa Seni Keagamaan di IAKN Kupang - Papadja, Anita; Dersy Rejoice Taneo; Marsya Phventa Manafe (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2025)
This study aims to analyze the variation skills possessed by students of the Religious Arts Education program in the Microteaching course at the State Christian Institute of Theology (IAKN) Kupang in 2025. This research is descriptive qualitative, aimed at exploring and understanding the basic skills of applying variations implemented by students as prospective teachers. The analysis not only provides a general overview but also reveals the complexity of the basic skills applied in teaching practice. The results of the study show that out of seventeen students who conducted microteaching practices, 90% of them understand and master the skills of applying variations, particularly in teaching style variations such as the use of voice variation, attention focusing, and silence. This study also found that a dynamic teaching style can enhance student engagement. Furthermore, variations in the use of media and teaching materials, including those that can be seen, heard, and touched, provide a more comprehensive learning experience for students. This research is expected to contribute to the development of students' teaching skills in the future.